ESG disclosure and firm value in southeast asian banking firms: Does board independence matter? - Wibowo, Sigit Arie; Wulandari, Susila Tri; Gutiérrez-Ponce, Herenia (Journal of Accounting and Investment, 2026)
Research aims: This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on firm value and to analyze the moderating role of board independence in Southeast Asian banking companies.Design/Methodology/Approach: This research employs a quantitative approach using panel data from banking companies in Southeast Asia (Indonesia, Malaysia, Singapore, Thailand, and the Philippines) over the period 2010–2023. ESG data are obtained from Thomson Reuters, while firm value is measured using Tobin’s Q. Panel regression analysis is conducted using EViews.Research findings: The results indicate that ESG disclosure has a positive and significant effect on firm value. However, the individual ESG dimensions show varying results, where social disclosure negatively affects firm value, while environmental and governance disclosures are insignificant. In addition, board independence strengthens the relationship between ESG disclosure and firm value, suggesting that governance quality plays an important role in enhancing the effectiveness of sustainability practices.Theoretical contribution/Originality: This study contributes to the ESG literature with providing evidence from Southeast Asian banking firms, an emerging market context that remains underexplored in prior studies. Furthermore, this study extends the literature by demonstrating that board independence functions as a governance mechanism that determines the value relevance of ESG disclosure.Practitioner/Policy implication: The findings provide important insights for regulators, investors, and banking institutions regarding the importance of strengthening governance structures to ensure that ESG initiatives create long-term firm value. The results also support the development of more effective sustainability reporting and governance policies in the banking sector.Research limitation/Implication: This study is limited to banking sector data and ESG scores from a single database. Future research may expand to other sectors and alternative ESG measurement approaches.